Further education colleges and leadership: Checking the ethical pulse (UCL Press, 2016)
In this paper, I check the ethical pulse of further education (FE) at the moment of its coming of age. Using a philosophical lens, I select and review post-2010 literature, to argue that FE colleges persist in a diminished form within a learning economy. In response to the managerial onslaught, the sector has adopted an ethics of survival, a necessary response to austerity and deregulation. Twenty-one years after incorporation, ethical fading has purged ethical desire from educational discourse, while the endless banality of college life has corroded the language with which it might be possible to speak about educational purpose, value, utopia, democracy, equity, and vision.